REPRESENTASI BUDAYA INDONESIA DALAM IKLAN ANIMASI KHONG GUAN VERSI "SEBUAH KENANGAN MANIS" (Kajian Semiotika Roland Barthes) - Muhammad Hadyan Alfaridzi, (2022)
The background of this research explains how Khong Ghuan's animated advertisement entitled "A Sweet Memories" represents Indonesian Culture. Khong Guan's animated advertisement entitled "Seboah Kenangan Manis" is a unique advertisement in the form of animation that adopts the type of Japanese anime by incorporating elements of Indonesian culture. The animated Khong guan advertisement entitled "A Sweet Memories" tells the story of the warmth of a family whose husband and wife grandparents are tidying up the house and also relaxing on Eid al-Fitr while the grandfather remembers their youth and the two of them communicate remotely with their children, in-laws and grandchildren. The purpose of this study was to determine the representation of Indonesian culture in the animated advertisement of Khong Guan version "Seboeah Kenangan Manis". The theory used in this research is Roland Barthes' Semiotic Theory (Meaning of Connotation, Meaning of Denotation, and Myth). The research methodology used is a qualitative approach, the type of descriptive research, and the primary and secondary data collection methods. The results of the semiotic analysis in this study indicate that there is a representation of Indonesian culture that shows the diversity of Indonesian cultural elements depicted in this advertisement. Keywords: Advertising, Representation, Roland Barthes' Semiotic